Investigating the mechanism of impact and differential effect of the Quality Premium scheme on antibiotic prescribin in England: a longitudinal study. Issue 3 (August 2020) - Anyanwu, Philip Emeka; Majeed, Azeem; Hopkins, Susan; Pouwels, Koen; Hayhoe, Benedict W J; Mcleod, Monsey; Crine, Sarah Tonkin-; Costelloe, Céire; Moore, Michael; Walker, Anne; Borek, Aleksandra
No abstract available